SOCIAL CAPITAL, EDUCATION AND CHOICE JOB SEARCH METHODS IN SENEGAL - Diop, Mame Sangone; Dramani, Latif (American Economic & Social Review, 2023)
The objective of this paper is to analyze the microeconomic impact of education on well-being, as measured by social capital in terms of the different means used to search for a job in Senegal. The endogenous variable (social capital) is categorized into four sub-modalities represented as follows: « Personal relations », « Advertisements-firms » composed of advertisements/media/internet and applications to firms; « Agencies-State » composed of the civil service, the employment office, private placement agencies and competitions/tests; and « Other » composed of the search for partners, the search for financing or any other means. The exogenous characteristic variables are the different levels of education (primary, middle, secondary and higher), the gender, the age and the marital status of the individuals aged at least 15 years. The data come from the ANSD's (2020) Senegal Poverty Monitoring Survey database on a sample of 168,203 individuals. Using Stata, the results obtained through estimation by the multinomial logistic method (MLM) show that only higher education has a positive and significant impact on all the means used to look for a job in Senegal, but at different levels and probabilities. This article suggests a strong expansion of networks of acquaintances and mutual aid because the higher the individual's social capital, the more chance he has of interacting with others, broadening his contacts and improving his well-being. Combined with a higher level of education, it offers job-seekers more opportunities to succeed in their search.JEL Classification Codes: A13, I31, I21, D90, C51.